2023
DOI: 10.3390/polym15061583
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Series of Self-Healable Bio-Based Poly(thiourethane) Vitrimer-like Materials

Abstract: A series of poly(thiourethanes) (PTUs) from biobased monomers have been synthesized. Limonene and squalene were transformed into polyfunctional thiols by thiol-ene reaction with thioacetic acid and further saponification. They were then reacted in different proportions with hexamethylene diisocyanate (HDI) in the presence of a catalyst to prepare bio-based poly(thiourethane) vitrimer-like materials. The different functionalities of squalene and limonene thiols (six and two, respectively) allow for changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Over the past few years, Serra and co-workers ,, have shown that these materials exhibit vitrimeric-like behavior, characterized by the dissociation of the thiourethane group into isocyanate and thiol. This process is followed by rapid reformation, resulting in a decrease in viscosity upon heating, following an Arrhenius-type evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, Serra and co-workers ,, have shown that these materials exhibit vitrimeric-like behavior, characterized by the dissociation of the thiourethane group into isocyanate and thiol. This process is followed by rapid reformation, resulting in a decrease in viscosity upon heating, following an Arrhenius-type evolution.…”
Section: Resultsmentioning
confidence: 99%
“…PTUs are synthesized through the condensation of isocyanates and thiols, resulting in materials with dynamic properties facilitated by thiourethane–thiourethane or thiol–thiourethane exchange reactions . Since the initial report in 2019 by Torkelson’s group, various thiol–isocyanate systems with dynamic properties have been investigated, employing different catalysts and exploring sustainable alternatives. In the quest for more sustainable materials, there have been reports on substituting monomers derived from biomass for those derived from fossils, along with the development of non-isocyanate poly­(thiourethane)­s (NIPTUs). , Additionally, dynamic PTUs have been employed as a polymeric matrix in nanocomposites …”
Section: Introductionmentioning
confidence: 99%
“…For this, Guerrero et al employed 9 that facilitates the thermal decomposition of the imidazolium salt at temperatures above 100 °C. 17 This process results in the liberation of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), which serves as a basic catalyst for the transthiocarbamoylation exchange reaction. 17,33…”
Section: Thermal-latent Catalystsmentioning
confidence: 99%
“…17 This process results in the liberation of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), which serves as a basic catalyst for the transthiocarbamoylation exchange reaction. 17,33…”
Section: Thermal-latent Catalystsmentioning
confidence: 99%
See 1 more Smart Citation